Pengaruh Subsitusi Tepung Labu Siam (Sechium Edule) Terhadap Daya Terima Biskuit - Kia, Anugerah Theodora; Talahatu, Anna Henny; Purnawan, Sigit (Jurnal Kesehatan Madani Medika, 2025)
Chayote (Sechium edule) is one of the local food ingredients that has the potential to be used as an alternative substitute for wheat flour in making biscuits. The use of chayote flour is expected to increase the nutritional value and diversify local-based food. This study aims to determine the effect of substitution of wheat flour with chayote flour on the organoleptic value of biscuits, especially on the parameters of color, aroma, taste, and texture. This study used an experimental method with a completely randomized design consisting of four treatments of chayote flour substitution, namely 0% (P1), 25% (P2), 50% (P3), and 75% (P4). The data obtained were analyzed using the Kruskal-Wallis test and the Mann-Whitney further test to see the differences between treatments. The results showed that the substitution of chayote flour had a significant effect on color, aroma, and taste (p <0.01), but did not have a significant effect on texture (p>0.01). Treatment P1 had the highest acceptability, while P4 had the lowest level of acceptability. The use of chayote flour in biscuit making can be applied up to an optimal limit of 50% to maintain organoleptic characteristics and increase fiber content. Further research is recommended to explore processing techniques that can improve sensory acceptance and nutritional value of biscuits with chayote flour substitution.